Prosecution of SANDF soldiers by South African military courts for violations of un sexual abuse and exploitation during peacekeeping operations - Botha, C.J. (Christo) (University of Pretoria, 2020)
Mini Dissertation (LLM)--University of Pretoria, 2019.